Humanitarian activity as a ‘soft power’ instrument of transnational corporations - N. O. Yudin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Globalization has turned transnational corporations (TNCs) into the key actors in the world economy and at the same time strengthened their political ambitions. In order to establish a monopoly over certain markets, create opportunities for additional revenue growth and geographic expansion, TNCs are actively using a wide range of political instruments, in which various humanitarian projects and initiatives play an increasingly important role. In this context, it seems appropriate to consider the humanitarian activities of TNCs through the lens of the concept of soft power. The first section of the paper examines the views of Russian and foreign experts on the role of political considerations in the humanitarian initiatives of TNCs, as well as on the possibility of achieving a balance between the development goals of host countries and the interests of foreign capital. The author shares the view of those scholars who argue that the humanitarian activities of TNCs can not only create a favorable political climate for the corporation in the host country, but also subtly introduce Western (globalist) narratives into the public consciousness. The second section examines the activities of Nestle in Colombia as an example of effective use of the humanitarian agenda to promote the economic and political interests of TNCs in developing countries. The author shows that within the framework of corporate humanitarian expansion Nestle implemented a wide range of humanitarian projects, which allowed it not only to secure a foothold in the Colombian market, but also to penetrate its political system, as well as to gain opportunities to further expand its political presence in the region. The author concludes that the growing influence of TNCs erodes the government structures and may even put into question the political sovereignty of their host countries. In this context, the Russian authorities should not only be very cautious about the activities of TNCs on its territory, but also provide a clear legal framework regulating the presence of transnational businesses in the humanitarian space of the country. The third section outlines a set of principles that, if implemented, could minimize the opportunity for TNCs to influence political processes in the Russian Federation through the use of various humanitarian actions and projects as a tool of soft power.